2015
DOI: 10.1016/j.abb.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Roles of active site residues in LodA, a cysteine tryptophylquinone dependent ε-lysine oxidase

Abstract: Site-directed mutagenesis identified residues in the substrate channel of LodA that play multiple roles in regulating Km values of substrates, kcat and the extent of biosynthesis of the protein-derived cysteine tryptophylquinone (CTQ) cofactor. Mutations of Cys448 increase Km values for lysine and O2, with the larger effect on Klysine. Tyr211 resides within a mobile loop and is seen in the crystal structure of LodA to form a hydrogen bond with Lys530 that appears to stabilize its position in the channel. Y211F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…In contrast to what was observed with GoxA, no complex of LodA or LodA precursors with LodB was observed during purification. Interestingly, the preparation of pure LodA was found to contain a significant fraction of a precursor that lacked CTQ but no LodB 18 . Thus, while preLodA and LodB must also interact to achieve CTQ biosynthesis, the complex formation between those two proteins must be transient as was the case with preMADH and MauG, and different from what was observed for precursor GoxA-GoxB complex.…”
mentioning
confidence: 99%
“…In contrast to what was observed with GoxA, no complex of LodA or LodA precursors with LodB was observed during purification. Interestingly, the preparation of pure LodA was found to contain a significant fraction of a precursor that lacked CTQ but no LodB 18 . Thus, while preLodA and LodB must also interact to achieve CTQ biosynthesis, the complex formation between those two proteins must be transient as was the case with preMADH and MauG, and different from what was observed for precursor GoxA-GoxB complex.…”
mentioning
confidence: 99%
“…This was verified by the crystal structure of LodA with the lysine-CTQ adduct formed (9). The roles of residues in and around the active site of the LodA in catalysis and CTQ biogenesis were identified by site-directed mutagenesis (10).…”
mentioning
confidence: 78%
“…Phe-237 is of interest because it corresponds in the primary sequence to Tyr-211 of LodA (Fig. 2), which is conserved in most Group I proteins and which strongly influenced the K m values of both lysine and O 2 for LodA (10). In the homology model, the position of Phe-237 is not structurally conserved with Tyr-211 in LodA, as are the positions of CTQ, Asp-547/Asp-512 and His-466/Cys-448 (GoxA/LodA numbering, respectively).…”
Section: Structural Comparisons Of Goxa With Lodamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is shown that the total soluble D512A LodA exhibits no significant specificity for binding copper over other metals. It was previously shown that mutagenesis of other residues, such as Cys448, in the active-site and substrate channel of LodA effect the levels of mature CTQ present in the enzyme as well as kinetic parameters for the catalytic reaction 42 . Thus, perturbations of the positions of other residues in the active site which are caused by the D512A mutation or binding of a metal other than copper could also abolish the initial hydroxylation.…”
Section: Discussionmentioning
confidence: 99%